DAYA TERIMA BROWNIES TEPUNG BIJI KECIPIR DAN KANDUNGAN GIZINYA - elvira dewinta indria; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Wing bean is a plant that started forgotten and not used. Wing bean only used as seed and the rest thrown away. Wing bean contain proteins that similar to soy bean’s proteins, amount 32,8 mg. Therefore, wing bean processed into brownies to make wing bean more used and increase the nutritional value of brownies. The aim of this researched were to know acceptable of wing beans’s brownies. The type of this researched were experiment using a completely randomized design. Panelists in this research are 30 people. Data received processed manually and analyzed by using descriptive analysis percentage. The result showed that the organoleptic test based on taste, scent, colour, and texture, the panelists like the wing bean’s brownies with percentage of taste 93,3 %, scent 82,3 %, colour 88,9 % and texture 96,7 %. Based on calculating using nutrisurvey of 100 gr material, obtained energy 289,5 kcal, protein 10,1 gr  carbohydrate 20,8 gr and fats 27,0 gr. The conclusion of this researched were the taste, scent, colour and texture of wing bean’s brownies liked. Wing bean’s brownies has advantages than wheat flour brownies, because the energy and carbohydrate is lower than wheat flour brownies and the protein is higher than wheat flour brownies. Suggestions of this research is the people can use the wing bean brownies as the alternative of meal that high protein and low carbohydrate. Moreover, it need future research to reduce the original scent of wing bean flour. Keyword : Acceptibility test, Brownies, Wing bean, Nutrient Content